Analisis Pengaruh Pembiayaan, Kualitas Pelayanan dan Motivasi Terhadap Loyalitas dan Kesejahteraan Anggota Koperasi Pondok Pesantren Muhammadiyah Kota Binjai - Bakara, Windy Okanawa; Sugianto, Sugianto; Ahmadi, Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The purpose of this study was to determine the effect of financing, service quality and motivation on the loyalty of members of the Muhammadiyah Islamic boarding school cooperative and to determine the effect of financing, service quality and motivation on the welfare of members of the Muhammadiyah Islamic boarding school cooperative. This type of research is quantitative using descriptive analysis method and the number of samples is 85 people. Distribution of questionnaires to respondents in this study using random sampling technique. The data used is primary data obtained from the results of distributing questionnaires to respondents, namely members of the Muhammadiyah Islamic Boarding School cooperative in Binjai City. Then the data that has been successfully collected is tested with the SPSS23 application tool. This study obtained the results that the financing variable has a positive effect on the loyalty of members of the Muhammadiyah Islamic Boarding School cooperative in Binjai City, the service quality variable has a positive effect on the loyalty of members of the Muhammadiyah Islamic Boarding School cooperative in Binjai City, and the motivational variable has no effect on the loyalty of members of the Muhammadiyah Islamic Boarding School cooperative in Binjai City. Furthermore, the financing variable has a positive effect on the welfare of members of the Muhammadiyah Islamic Boarding School cooperative in Binjai City, the service quality variable has no effect on the welfare of members of the Muhammadiyah Islamic Boarding School cooperative in Binjai City, and the motivational variable has a positive effect on the welfare of members of the Muhammadiyah Islamic Boarding School cooperative in Binjai City